2020
DOI: 10.1177/1527002520948108
|View full text |Cite
|
Sign up to set email alerts
|

The AFL Pick Trading Market as a Coasian Utopia

Abstract: Sporting leagues have various competitive balance measures including player drafts, where teams are awarded picks based on prior performance. Teams, however, have the option to either exercise this pick or trade it as they see fit. An analysis of this trading market in the NFL stated that players obtained through traded picks contributed more to their recruiters in comparison to their counterparts. This paper retested this within the AFL and disproved this fact, establishing the Coasian notion of the efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Moreover, the decline in pick value observed under the survival estimate function in Figure 2 is much less than that proposed in the current AFL DVI (AFL, 2015). This further validates the claims made by Chandrakumaran (2021) that the choice of career compensation to create the league's DVI does not properly describe pick value. On the other hand, similar to the previous author's model, the lower rate of decline further suggests that it is in the best interest of a team to trade down and select players using later picks, which is against conventional wisdom.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Moreover, the decline in pick value observed under the survival estimate function in Figure 2 is much less than that proposed in the current AFL DVI (AFL, 2015). This further validates the claims made by Chandrakumaran (2021) that the choice of career compensation to create the league's DVI does not properly describe pick value. On the other hand, similar to the previous author's model, the lower rate of decline further suggests that it is in the best interest of a team to trade down and select players using later picks, which is against conventional wisdom.…”
Section: Discussionsupporting
confidence: 81%
“…The index thereby created a benchmark for teams which utilised the PAS rules to surrender picks which represented the competing bid by a rival club and for those who simply exchanged selections between each other. Even though this system did show traits of overvaluing early selections (Chandrakumaran, 2021), like those observed in the NFL's pick value chart (Massey & Thaler, 2013), it did not address the comparison of draft picks and active players similar to its academic counterparts discussed in footnotes 2 and 3, further validating the need for this study.…”
Section: Draft Value Indexmentioning
confidence: 79%
See 1 more Smart Citation
“…Researchers have reaffirmed this phenomenon in the NBA [ 7 – 9 ] and other sporting competitions such as the NFL [ 10 , 11 ], National Hockey League (NHL, [ 12 ]) whilst Borland et al [ 13 ] showed minimal effects in the Australian Football League (AFL). However, Chandrakumaran [ 14 ] concluded that this effect might prevail in the AFL as the difference between inferred and actual value was lesser for early picks (similar to the NFL [ 3 ]). This was attributed to the overutilisation of players selected early on in the draft to justify the initial choice.…”
Section: Introductionmentioning
confidence: 99%
“… 7. See Surdam (2006), Booth (2009), Lin & Chang (2011), Schmidt (2011), and Chandrakumaran (2021). Some are quite dramatic on this point.…”
mentioning
confidence: 99%